Do we need an ethics of planetary sustainability?. (2019) - Beisbart, Claus
Abstract: The politics of the United Nations aims at sustainable development (i.e., development that can continue with future generations). Andreas Losch has recently proposed to expand our current notion of sustainability to what he calls 'planetary sustainability', and he has urged an ethics of planetary sustainability. This comment article discusses these proposals. The proposed conceptual change is assessed, drawing on desiderata suggested by Carnap. To the extent to which the current notion of sustainability has excluded consideration of outer space, we gain in simplicity. To the extent to which it has been unclear about this issue, we gain in exactness. The proposed concept is fruitful because it points to important considerations, in particular if there are extra-terrestrial beings that share moral status with human beings. But to some extent this fruitfulness requires a clear deviation from the anthropocentric outlook of our current notion of sustainability, and costs regarding similarity arise. As far as an ethics of sustainability is concerned, we certainly need to address ethical issues that arise in relation to outer space. However, the notion of planetary sustainability is not likely to figure prominently in related thoughts because the notion of sustainability is not a key concept in known ethical theories.